Digital image processing - Gonzalez, Rafael C.; Wintz, Paul A. (Pearson Education Limited, 2018)
For courses in Image Processing and Computer Vision. Introduce your students to image processing with the industry's most prized text For 40 years, Image Processing has been the foundational text for the study of digital image processing. The book is suited for students at the college senior and first-year graduate level with prior background in mathematical analysis, vectors, matrices, probability, statistics